The dynamics of radial growth of three selected tropical tree species studied through knife-cutting method - Wang, Kang Han; Sahri, Mohd Hamami; Salleh @ Japri, Mohd Nazre (Universiti Putra Malaysia Press, 2013)
Tropical trees which lack distinct growth rings have caused difficulty in estimating the growth rate of those trees. This has resulted in limited knowledge concerning tropical tree growth pattern and rate of increment. This study aimed to assess the radial growth and cell production rate of three selected tropical species, namely, Macaranga gigantea, Endospermum diadenum and Dipterocarpus costulatus, with different diameters at breast height. For this purpose, knife-cutting method was adopted in this study. A knife was inserted through the bark into the outer xylem of a tree to wound the cambium and remove immediately. Wood discs containing wound area were collected from living trees after a period of time. Transverse sections of 20-25 µm in thickness were obtained through sliding microtome and dehydrated in a graded series of ethyl alcohol before staining with safranin and fast green. Dibutyl phthalate xylene (DPX) was used as a mounting medium for preparation of permanent microscope slides. The species-related anatomical response to wounding was identified and used to define the time of marking. Results show that radial growth rate and cell production rate varied across species and tree sizes. M. Gigantean and E. Diadenum showed faster growth rates than D. Costulatus, especially in small diameter classes. Meanwhile, D. Costulatus had the lowest growth rate and cell production rate. Thus, both the pioneer species are thus considered to grow faster in smaller stem size than larger stem size, while the study succeeding species grow faster in larger stem size than smaller stem size.